Characteristics of MOCVD-Grown High-Quality CdTe Layers on GaAs Substrates - P. W. Sze; K. F. Yarn; Y. H. Wang; M. P. Houng; G. L. Chen (Active and Passive Electronic Components)
CdTe epitaxial layers are grown successfully on a (100)-GaAs substrate by metalorganic chemical vapor deposition (MOCVD) using dimethylcadrnium (DMCd) and diethyltelluride (DETe) as alkyl sources. The CdTe epilayers grown between 365°C and 380°C possess the best surface morphology. DETe is used as the controlling species of this growth system. Typical growth rates are varied from 2.51µm/hr to 5.31µm/hr. Low-temperature (12K) photoluminscence (PL) measurements reveal that 380°C is the best growth temperature and the full width at half maximum (FWHM) of the dominated peak is about 1.583eV by the bound-exciton emission of 9.38meV. The double crystal X-ray rocking curves (DCRC) indicate that the FWHM decreases while increasing the epilayer thickness and approaches a stable value about 80 arc sec under the growth rate of 5.2µm/hr, the growth temperature of 380°C and the DETe/DMCd concentration ratio of 1.7. The value of 80 arc sec in FWHM is the smallest one ever reported to date.